Efektivitas Peran Koperasi dalam Pengembangan Usaha Kecil di Kota Medan - Raniwati Siregar; Marliyah Marliyah (Universitas Dehasen Bengkulu, 2022)
This study aims to determine the role and effectiveness of small business development in the Department of Cooperatives and SMEs in Medan City and to determine the effectiveness of developing cooperatives and small and medium enterprises in the Department of Cooperatives and Small and Medium Enterprises in Medan City. This study uses a qualitative method, in which the researcher wants to know how the Effectiveness of the Role of Cooperatives in the Development of Small Business in Medan City is. Thus, through this qualitative research, the researcher tries to describe the problems that exist in relation to the Effectiveness of the Role of Cooperatives in the Development of Small Business in Medan City. The Regional Government along with the Cooperatives and SMEs Office work together to develop the progress of Medan City SMEs. Therefore, the main task of the Medan City Cooperatives and SMEs Service is to carry out regional autonomy in carrying out all the assisting tasks that have been given by the central government and from the provincial government. As for the consequences of these activities, the Department of Cooperatives and SMEs are obliged to carry out all program activities that aim to increase the potential of the SME sector, especially in the urban village of Medan.